Public health genomics capacity assessment: readiness for large-scale pathogen genomic surveillance in Canada’s public health laboratories - Nadon, C.; Croxen, M.; Knox, N.; Tanner, J.; Zetner, A.; Yoshida, C.; Van Domselaar, G. (BMC public health, 2022)
Background Along with rapid diagnostic testing, contact tracing, and public health measures, an effective pandemic response incorporates genomics-based surveillance. Large-scale SARS-CoV-2 genome sequencing is a crucial component of the global response to COVID-19. Characterizing the state of genomics readiness among Canada’s public health laboratories was necessary to inform strategic planning and deployment of capacity-building resources in the early stages of the pandemic. Methods We used a qualitative study design and focus group discussions, encompassing both technical and leadership perspectives, to perform an in-depth evaluation of the state of pathogen genomics readiness in Canada. Results We found substantial diversity in the state of readiness for SARS-CoV-2 genomic surveillance across Canada. Despite this variability, we identified common barriers and needs in the areas of specimen access, data flow and sharing, computing infrastructure, and access to highly qualified bioinformatics personnel. Conclusions These findings enable the strategic prioritization and deployment of resources to increase Canada’s ability to perform effective public health genomic surveillance for COVID-19 and prepare for future emerging infectious diseases. They also provide a unique qualitative research model for use in capacity building.